ANALYSIS OF ANTERIOR FACIAL HEIGHT DIMENSION BASED ON SKELETAL CLASSIFICATION OF CIMAHI WEST JAVA POPULATION - Darwis, Rudi S; Suntana, Mutiara Sukma; Dewi Fajar, Ghaida (Journal of Health and Dental Sciences, 2024)
Dento-facial aesthetics is an essential aspect of contemporary orthodontics, reflected by increasing demands for many aspects of patient's aesthetic improvement. Facial vertical height determines an individual's aesthetics and is vital to establishing facial harmonies. One of the facial vertical problems is related to anterior facial height. Vertical facial height is strongly influenced by the vertical position of the maxilla and mandible, so that it can be affected by the relation between the skeletal jaw. This study aims to determine the difference between the anterior facial height and the skeletal jaw relation. Based on different skeletal classifications by Steiner skeletal analysis, measurements on lateral cephalometric radiographs by comparing and connecting the anterior facial height. This research used an analytic-cross-sectional study with total sampling from 2019-2021. Fifty lateral cephalometrics between 18 and 41 years of age patients, with inclusion criteria, were included in this study. Each sample was analyzed using Steiner's skeletal classification, and the AFH and PFH were measured. The study result showed that 30% of the sample had skeletal class I malocclusion, 42% had skeletal class II, and 28% had skeletal class III. The mean score by skeletal classification for LAFH was 66.92 mm, the mean of UAFH was 50.22 mm, and the mean TAFH was 114.02. Based on the analysis results, there was no significant difference between anterior facial height (UAFH, LAFH, and TAFH) based on skeletal classification. DOI : 10.54052/jhds.v4n1.p57-68